" تاثير برنامج تمرينات تأهيليه داخل الماء والتنبيه الکهربائي علي المصابين بسقوط القدم" The effect of a rehabilitation exercise program in water and electrical stimulation For those with a fallen foot - تقوي کمال سيد (Beni-Suef University, Faculty of Physical Education, 2022)
يهدف البحث إلى تصميم برنامج بدنى تأهيلى داخل الماء والتنبية الکهربائي علي المصابين بسقوط القدم، والتعرف على أثر البرنامج التأهيلي لمعالجة اصابة سقوط القدم، وقد أستخدمت الباحثة المنهج التجريبي، لملامته لطبيعة البحث بإستخدام القياس القبلى والقياس البعدى لمجموعة واحدة، على عينة قوامها (6) مصابين تقاربت أعمارهم بين ( ٢٠-٥٠ ) سنة، أسباب الجلطة متفاوتة بين عينة البحث فمنهم بسبب ( ارتفاع ضغط الدم الشرياني، اصابة ثانوية نازفة في الدماغ أو جراحة فى الدماغ في الدماغ لاستئصال ورم معین، عجز القلب الوعائي)، ومن وسائل وأدوات جمع البيانات جهاز الجونيوميتر، جهاز الدينامومتير، جهاز الشمع الطبي، جهاز التحفيزات الکهربائية للعضلات والأعصاب المحيطة، حمام الماء البارد والحار، وقد أسفرت النتائج إلى أن ممارسة التمارين العلاجية المعدة ضمن برنامج علاجي مرکز ومتکامل يکون له تأثير ايجابي على تحسين زاوية الثني الظهري للکاحل عند الأشخاص المصابين باصابة سقوط القدم نتيجة لإصابة عصب مرکزي أو محيطي وکذلک مرونة واطالة العضلات الظنبوبية الخلفية والوتر الاخليلي، إن صياغة مفردات البرنامج التأهيلي وادخال وسائل مساعدة مع التمارين العلاجية وتوظيفها بشکل علمي له تأثير ايجابي على تحسين درجة القوة العضلية للعضلات العاملة على رفع القدم والثني الظهري لمفصل الکاحل. The research aims to design a rehabilitative physical program in the water and electrical stimulation for those with foot fall, and to identify the effect of the rehabilitation program to treat a foot fall injury. Their ages ranged between (20-50) years, the causes of thrombosis vary among the research sample, some of them are due to (arterial hypertension, secondary hemorrhagic brain injury or brain surgery in the brain to remove a specific tumor, cardiovascular deficit). Goniometer, dynamometer, medical wax device, electrical stimulation device for surrounding muscles and nerves, cold and hot water bath. The results showed that practicing therapeutic exercises prepared within a focused and integrated treatment program has a positive effect on improving the angle of dorsal flexion of the ankle in people with a fall injury. The foot as a result of injury to a central or peripheral nerve, as well as the flexibility and lengthening of the posterior tibial muscles and the achilles tendon. Therapeutic Marine and its scientific use has a positive effect on improving the degree of muscular strength of the muscles working on raising the foot and flexing the dorsal ankle joint.